Características comerciales y oportunidades de mercado para las comercializadoras de implementos deportivos del sector la estación en la ciudad de Riobamba, provincia de Chimborazo, período 2016. - García Chávez, Dennys Renato (2018)
The marketers of sports inputs of the sector the Station are MIPYMES that provide a great contribution to the local economy of the city of Riobamba, the main characteristic of these organizations is that they do their work in a craft form, which limits the responsiveness, owing to the lack of documented marketing strategies to maintain and improve market opportunities, leading organizations to generate levels of customer dissatisfaction, which is linked to indices of ignorance in specific functions of each employee that operate in the different MIPYMES. In this case the workers do not use commercial strategies of customer relationship seller, for this reason the loyalty of the consumer is not present in any of the sports marketers. For these reasons the importance of this document is evident, which covers aspects of continuous improvement, empowerment within the target market and linkage with new business advantages, hence the purpose of this research is to determine how the commercial characteristics affect the market opportunities for the marketers of sports implements in the sector the Station in the city of Riobamba.